Social tourism and its contribution to sustainable tourism - McCabe, Scott (Ministry of Economy, Industry and Competitiveness, Spain, 2018)
Social Tourism has gained wide recognition for the benefits it brings to citizens who would otherwise not be able to participate in tourism. Social tourism also delivers benefits to the tourism industry, to destinations and to provide a positive return on investment for governments. However, whilst policy makers extol the virtues of social tourism, programmes have struggled to remain resilient under pressure on public finances caused by the Global Financial Crisis. This paper reviews the contributions of social tourism to sustainable tourism, critically assesses their potential to drive sustainable tourism in the future and makes recommendations for European policy makers.